الاصلاح الاقتصادي في دول متقدمة مختارة وإمكانية الاستفادة منها في الاقتصاد العراقي (المجلة العراقية للعلوم الاقتصادية, 2018)
After many changes, which the world countries witnessed, regardless of their level of development in all areas and in the economic field, in particular, and across time periods not so short , the governments of those countries became aware that they must undertake many appropriate regulations, and in various levels to meet these changes, seeking by that to follow the accelerating global pace, which leaves behind a lot of those who does not do what is proper with that, and it is represented, in general, in adopting different multi-faceted policies in terms of the impact, in order to work on creating the right and required environment, according to the size of the changes and the expected effects from them.And especially those related to economic reform, and what the latter requires for designing the programs, and identifying the necessary means to be implemented, while giving importance to those experiences attributed to these countries, which have achieved successes in this area (reform) to take advantage of them in terms of adapting what has been implemented to reach the desired goals, and serving their own designed programs, in addition to not neglecting those experiences that have not achieved success, as well as it will benefit from studying the factors that led to the failure, or obstructed their success at the desired level and significance.What has been just stated is applied on the Iraqi reality, in general, and its economy, in particular, as what has been accumulated within it – over years considered not to be short - from inappropriate effects, resulting from imbalanced levels of the performance of various governments, which successively managed its economy, made the latter to be in an urgent need to achieve a radical reform for transforming from a one-sided (yield) economy to a multilateral one, taking advantage of the changes (which can be accurately identified by the latitudes, and, in particular, since the eighties of the last century) in the price of the main (and the most important) source of its budget revenues, represented in oil, to establish the right and scientific base for its infrastructure for enabling the country to rely upon it, to build a strong economy with a diversified productive structure, in contrast to what it was existing before, and what it is present